2015
DOI: 10.1680/macr.14.00170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment of MSWI bottom ash for its use in concrete

Abstract: In this paper, municipal solid waste incineration (MSWI) bottom ash was characterised before and after chemical treatment and the effect of ash addition on the performance of concrete as a partial replacement of fine aggregate was evaluated. The chemical treatment aimed to eliminate the side effect of MSWI ash -the creation of a network of bubbles -which can eventually lead to a significant reduction of the overall performance of concrete.Petrographic examinations, energy dispersive X-ray spectroscopy and X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…As such, metal extraction, washing and chemical treatments have been frequently required to minimize the hydrogen expansion by reducing the metallic aluminium content or stabilization by exhausting the expansive reactions before use. Measurement of the volume of hydrogen gas evolution and metallic aluminium content by Kim et al, (2015), showed effective reduction of both parameters after a chemical treatment with 1 mol/l of aqueous NaOH.…”
Section: Concretementioning
confidence: 99%
“…As such, metal extraction, washing and chemical treatments have been frequently required to minimize the hydrogen expansion by reducing the metallic aluminium content or stabilization by exhausting the expansive reactions before use. Measurement of the volume of hydrogen gas evolution and metallic aluminium content by Kim et al, (2015), showed effective reduction of both parameters after a chemical treatment with 1 mol/l of aqueous NaOH.…”
Section: Concretementioning
confidence: 99%
“…One of the beneficial utilisations of MSWI BA is in the area of road construction sector; for example, MSWI BA can be used the partial replacement of fresh fine aggregate mixed with Hot-Mix Asphalt (HMA) and Portland Cement Concrete (PCC) (Al An, Golestani, Nam, & Lee, 2015;Chen et al, 2008;Dubey & Townsend, 2007;Forteza, Far, Seguı´, & Cerdá, 2004;Hill, 2004;Kim, Tasneem, Nam, Yun, & Sohn, 2014;Kim, Nam, Al Muhit, Tasneem, & An, 2015;Li et al, 2012;Shi & Kan, 2009;Tasneem, Nam, & Eun, 2014;del Valle-Zermeño, Formosa, Chimenos, Martínez, & Fernández, 2013;Xue, Hou, Zhu, & Zha, 2009). Many studies have investigated both beneficial and side effects for the use of MSWI BA in HMA and PCC as an intact material (Al An et al, 2014An et al, , 2015Kim et al, 2014Kim et al, , 2015Kim et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated both beneficial and side effects for the use of MSWI BA in HMA and PCC as an intact material (Al An et al, 2014An et al, , 2015Kim et al, 2014Kim et al, , 2015Kim et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been made to reuse MSWI FA and BA in concrete as replacements for either Portland cement or fine and coarse aggregates [27,130,[140][141][142][143][144][145][146][147][148][149][150]. Because fine and coarse aggregates occupy 70-80% of the total volume in concrete, it can be advantageous to replace some of the aggregates with MSWI ash [125].…”
Section: Pccmentioning
confidence: 99%